Anxiolytic and sedative effects of sodium valproate with different experimental paradigms in male and female rats - María de losÁngeles Cintado; Luis Gonzalo De la Casa; Gabriel González (Neuropsychopharmacology Reports)
Abstract Valproic acid or sodium valproate is a widely used drug in the treatment of epilepsy, although it also appears to have anxiolytic and sedative properties derived from its agonistic action on the GABAergic system. To analyze these potential effects of the drug, we conducted three experiments with rats using procedures designed to assess anxiety in rodents. In the first experiment, with a fear conditioning procedure, three groups of male rats were included that received either 100 mg/kg or 300 mg/kg of valproate or an equivalent volume of saline solution. In Experiment 2, recording spontaneous activity in an open field, we compared the effects of valproic acid (300 mg/kg) on male and female rats. In the third experiment, we analyzed the effect of valproic acid using a novelty‐induced hypophagia test and tested again for potential differences as a function of the sex of the animals. The results showed an anxiolytic effect restricted to the 300 mg/kg dose of the drug in Experiment 1. Such an effect was restricted to the female sample in Experiment 2, but in the third experiment affected both sexes. As for the sedative effect, it was observed in all experiments irrespective of the sex of the rats. These findings hold significant implications for the treatment of anxiety disorders since valproate may offer a novel therapeutic approach for anxiety‐related conditions with distinct benefits and fewer side effects. However, clinical studies are needed to validate the translation of these findings from animal models to human patients.